Islam and Local Cultural Acculturation in the Indonesian Archipelago: A Study of Religious Traditions in Java, Kalimantan, and Sumatra - Purnamasari; Barkah, Sami (Al-fiqh, 2025)
The acculturation of Islam with local cultures in the Indonesian archipelago represents a unique historical phenomenon, distinct from the spread of Islam in other regions due to its peaceful, adaptive, and culturally embedded approach. This study aims to analyze and compare the patterns of Islamic acculturation with local traditions in three representative regions: Java (focusing on the Walisongo legacy and Slametan traditions), Kalimantan (specifically the Malay Sultanate of Sambas with its Tepuk Tepung Tawar and Saprahan rituals), and Sumatra (examining the Minangkabau philosophical-legal synthesis Adat Basandi Syarak, Syarak Basandi Kitabullah and Acehnese institutional dualism of Keuchik and Meunasah). Employing a qualitative library research method with a historical-comparative approach, this study analyzes primary sources such as ancient manuscripts (Salsilah Raja-Raja Sambas, Fathul 'Arifin), ethnographic literature, and contemporary scholarly works. The findings reveal three distinct acculturation typologies: cultural-dialogical in Java (negotiating form and substance), integrative-structural in Sambas (embedding Islam into ethnic identity and bureaucratic governance), and institutional-philosophical in Sumatra (resolving customary law with fiqh through legal compromise). Despite these divergent paths, the study confirms the unwavering preservation of Tawhid (the oneness of God) as the theological core, while Islamic jurisprudence (fiqh) demonstrated remarkable flexibility by utilizing the concepts of 'urf (local custom) and maslahah (public interest) to harmonize with local wisdom. This research validates the theories of "Pribumisasi Islam" (Indigenization of Islam) and Vernacularization, demonstrating that Islam in the archipelago enriched, rather than erased, local cultural identities. The study recommends further ethnographic research to explore the contemporary resilience of these acculturated traditions in the face of modernization and puritanical movements.